2016
DOI: 10.1161/jaha.116.003264
|View full text |Cite|
|
Sign up to set email alerts
|

Which QT Correction Formulae to Use for QT Monitoring?

Abstract: BackgroundDrug safety precautions recommend monitoring of the corrected QT interval. To determine which QT correction formula to use in an automated QT‐monitoring algorithm in our electronic medical record, we studied rate correction performance of different QT correction formulae and their impact on risk assessment for mortality.Methods and ResultsAll electrocardiograms (ECGs) in patients >18 years with sinus rhythm, normal QRS duration and rate <90 beats per minute (bpm) in the University Hospitals of Leuven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
295
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(317 citation statements)
references
References 26 publications
19
295
1
2
Order By: Relevance
“…This difference may be explained by the fact that we corrected the QT interval using both the Bazett and Fredericia formulas. The Fredericia formula has been proven to be superior to the Bazett formula, especiallyin terms of risk assessment for mortality [23]. In addition, in our cohort, we did not identify an increased incidence of arrhythmias or symptoms related to abnormal heart rhythms.…”
Section: Discussionmentioning
confidence: 44%
“…This difference may be explained by the fact that we corrected the QT interval using both the Bazett and Fredericia formulas. The Fredericia formula has been proven to be superior to the Bazett formula, especiallyin terms of risk assessment for mortality [23]. In addition, in our cohort, we did not identify an increased incidence of arrhythmias or symptoms related to abnormal heart rhythms.…”
Section: Discussionmentioning
confidence: 44%
“…Vanderbecket al have shown that Fridericia and Framingham correction provide the best rate correction for prolonged QT intervals and improved prediction of 30-day and 1-day mortality 15. In the setting of short QTc intervals, the association of different formulae with a higher probability of arrhythmic events remains to be proven, and assessing which one of the linear regression functions ( Framingham , Hodges or others8) to use, should be the aim of future research.…”
Section: Discussionmentioning
confidence: 99%
“…All adult patients (≥18 years) who had an ECG performed at the ED during a 3‐month period from 1 August, 2014 to 31 October, 2014, were eligible for inclusion in the study. QTc‐intervals >450 millisecond for men, and >470 millisecond for women were considered prolonged . The cutoffs were on the basis of the proposal by Goldenberg et al in 2006 and are supported by our previous work in a healthy subset determining an optimal reference interval for each formula .…”
Section: Methodsmentioning
confidence: 99%
“…In daily clinical practice, the Bazett correction formula (QTcB) is the most frequently used formula despite multiple reports of its limitations . There is a known overcorrection at high heart rates and a lack of correction for ventricular conduction defects (VCD) . This could lead to a large number of patients misclassified by automatic warning systems incorporating QTcB as having an increased risk and requiring more intensive medical follow‐up, whereas better correction formulas are available.…”
Section: Introductionmentioning
confidence: 99%